VEHICLE BODY DESIGN OF MOBILE WATER TREATMENT WITH ANALYSIS OF ITS STABILITY AND CHASSIS FRAME STRENGTH - SIDABUTAR (NIM : 23104014); Pembimbing : Dr. Ir. Bagus Budiwantoro, SILVESTER
The selection of vehicle to carry a Water Treatment Installation (WTI) is an important thing in a Mobile WTI design. Not only to satisfy the loading and space capacity, the stability as well as the strength of the chassis frame to support the load are also an important consideration. With mass totally Ã‚Â± 6600 kg and fixed WTI dimension, it is important to select a truck with GVM > 6600 kg and 1940 mm wide. The design of the body is needed because of the total mass, M and its distribution. And, the design of the jack frame is needed to support the load when WTI operated (WTI + water mass Ã‚Â± 8700 kg ). The fastener amount was calculated to fasten the load to the chassis frame safely. Then, analysis performed for stability and the strength of the vehicle chassis frame. Where, the center gravity (CG) location (totally: vehicle, WTI, body, etc) is a principal parameter on stability analysis beside thread and wheelbase. That is why, it is important to array the appropriate orientation and location of the load to generate the optimum CG. After all, with vehicle dynamic constraint and the load distribution, the strength of the chassis frame was evaluated to obtain the safety grade. The actual von Misses stress VM σ was compared to Yield Strength, y σ , and the maximum deflection was compared to the allowable deflection. Vehicle selection gave Dyna 125 LT and 115 ET (optional) as a result. With, assembly type (3) as an optimum load orientation and location for stability. Where, chassis frame support the load safely for all the loading case.